15 Ways To Pass Law School Exams In 3 Steps

3 simple ways to make first

For a start we will assume that G = (N, E, P, S) - unambiguous grammar and w=a1, a. an - a chain of L (G). Then there is the only sequence of the left removed chains of b0, b. bm, for which S=b0, bi, pi Yu bi+1 at 0 <=i

OPR: KS-grammar of G = (N, E, P, S) without e-rules is called as simple LL (k) - grammar (or the shared grammar) if for each AON all its alternatives begin various terminal symbols.

TRM: KS-grammar of G = (N, E, P, S) is LL (-grammar in only case when, when for two various rules A®b' and A®c' crossing of FIRST1 (b' FOLLOW1(A)) ZFIRST1 (with' FOLLOW1(A)) it is empty at all AON. (Without recreation center.